THE USE OF OLIVE OIL AS A PRESSURE INDICATOR PASTE MATERIAL IN CASES OF TRAUMATIC COMPLETE DENTURE ULCERS - Adinugraha, Irham Muhammad; Hasan Hapid, M; Sekar, Anindya (Fakultas Kedokteran Gigi Unjani, 2025)
Traumatic ulcers are a common complication in edentulous patients following the placement of complete dentures, often causing significant discomfort and leading to denture discontinuation. These ulcers typically result from ill-fitting dentures, overextended flanges, improper adaptation, or poor occlusal contacts. Management involves denture adjustment, temporary discontinuation of use, and the application of systemic or topical medications to promote healing. A critical step in denture adjustment is identifying excessive pressure areas using pressure indicator paste (PIP). This case report discusses the management of traumatic ulcers in a 60-year-old male patient utilizing a mixture of olive oil and zinc oxide powder as an alternative PIP. The patient presented with a painful ulcer on the lingual alveolar ridge of the mandible, which was exacerbated by denture use. Intraoral examination revealed a single white ulcer with erythematous edges. The denture was adjusted by reducing excessive areas identified using the olive oil-zinc oxide PIP and using Kenalog and Chlorhexidine gluconate 0.2% for ulcer healing. At the 7-day follow-up, the ulcer had healed, and the patient reported no pain. Using olive oil and zinc oxide as a PIP proved effective due to its non-setting properties and thick consistency, providing sufficient working time for precise adjustments. This mixture offers a practical and accessible alternative for identifying pressure points, ensuring optimal denture adaptation, retention, and stability. The case highlights the importance of addressing causative factors and utilizing innovative solutions for managing traumatic ulcers in complete denture wearers. DOI : 10.54052/jhds.v5n1.p69-78